Defense and Technical Cooperation Between Indonesia and Russia for the Defense and Security (2010-2015) - Ramadhan, Muhammad Iqbal; Maulina, Rizka (Tirtayasa Journal of International Law, 2023)
The rise of conflicts and crimes that threaten the sovereignty of the Republic of Indonesia is increasingly disturbing the defense and security of Indonesia. The weakening of the strength of the Indonesian National Army after the military embargo by the United States, France, and Germany made Indonesia feel the need to conduct military cooperation with other countries to improve the defense equipment and the quality of the Indonesian National Army as a means of National Defense. Russia, which is increasingly advancing in technology and military fields, has always sought the attention and support of developing countries in re-realizing its "superpower". This was used by Indonesia to re-establish "friendly" relations with Russia which had been tenuous during the new order in power in Indonesia. The purpose of writing this article is to find out what steps have been taken by both countries in conducting military cooperation, understand and explore various conflicts that could be a threat to the integrity and sovereignty of the Republic of Indonesia.  Furthermore, it also wants to know, understand, and describe how it affects various efforts to improve defense and security in Indonesia. The method used in this study is a descriptive research method. This research uses the library method (library research), the source of data for this research is entirely based on library research, books about literature. This research is based entirely on library research, books on foreign policy, the Indonesian Ministry of Foreign Affairs and other writings related to this research.  this research. The results of this study are: to improve the defense equipment and the quality of the Indonesian National Army in order to maintain and improve defense and security in Indonesia, the Indonesian government conducted military cooperation with Russia which was implemented into two forms of cooperation; Defense Cooperation and Military Technical Cooperation. The Indonesian-Russian government commission on Military Engineering cooperation has produced a memorandum of Understanding (MoU) on the commitment to procure the main tools of the Indonesian National Armed Forces weapons systems from Russia and in a visit to Moscow in December 2006